Identification of Pests and Diseases on Anthurium Jemani Ornamental Plants in the Ngledoksari Tawangmangu Tourism - Hanik, Nur Rokhimah; Fitriani, Rindi Diah Ayu; Oktavianingtyas, Desty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Anthurium decorative plants are presently exceptionally famous among fancy plant darlings, both from the appeal of the kind and variety and the exorbitant cost. In spite of the fact that nuisances and sicknesses in anthurium are not extremely upsetting, assuming left unrestrained it will significantly impede the magnificence, hinder development and be unfavorable to authorities and venders/business people of these elaborate plants. The motivation behind this study was to decide the sorts of nuisances and sicknesses that assault anthurium plants. This exploration was completed in the Desa Wisata NgledoksariTourism Town, Tawangmangu Regime, Karanganyar Rule, for 30 days from Saturday, December 01 to December 30, 2023. This study utilized 17 examples of Anthurium plants. The apparatuses utilized were cellphone cameras and writing material. The factors that will be noticed are nuisances and sicknesses that assault Anthurium. This examination utilized perception and interview methode, the information got were broke down by subjective clear. The consequences of this study found a few vermin and illnesses on anthurium establishes that made the plant leaves and blossoms have openings, withered, yellowed spots, foul, and caused hindered development. The irritations found were caterpillars and snails, while the sicknesses included growth, chlorisis, leaf rust, anthracnose, wavy leaves, and consumed leaves.